SERIES: eHealth in primary care. Part 3: eHealth education in primary care. (16th December 2020) - Houwink, Elisa J. F.; Kasteleyn, Marise J.; Alpay, Laurence; Pearce, Christopher; Butler-Henderson, Kerryn; Meijer, Eline; van Kampen, Sanne; Versluis, Anke; Bonten, Tobias N.; van Dalfsen, Jens H.; van Peet, Petra G.; Koster, Ybranda; et al.
Abstract: Background: Education is essential to the integration of eHealth into primary care, but eHealth is not yet embedded in medical education. Objectives: In this opinion article, we aim to support organisers of Continuing Professional Development (CPD) and teachers delivering medical vocational training by providing recommendations for eHealth education. First, we describe what is required to help primary care professionals and trainees learn about eHealth. Second, we elaborate on how eHealth education might be provided. Discussion: We consider four essential topics. First, an understanding of existing evidence-based eHealth applications and conditions for successful development and implementation. Second, required digital competencies of providers and patients. Third, how eHealth changes patient-provider and provider-provider relationships and finally, understanding the handling of digital data. Educational activities to address these topics include eLearning, blended learning, courses, simulation exercises, real-life practice, supervision and reflection, role modelling and community of practice learning. More specifically, a CanMEDS framework aimed at defining curriculum learning goals can support eHealth education by describing roles and required competencies. Alternatively, Kern's conceptual model can be used to design eHealth training programmes that match the educational needs of the stakeholders using eHealth. Conclusion: Vocational and CPD training in General Practice needs to build on eHealth capabilities now. We strongly advise the incorporation of eHealth education into vocational training and CPD activities, rather than providing it as a separate single module. How learning goals and activities take shape and how competencies are evaluated clearly requires further practice, evaluation and study.